FACTORS AFFECTING HOUSEWIVES ON PURCHASE DECISION AT ALFAMART BANJARMASIN - - Norrahmiati (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, The purpose of this research is to; (a) determine the influence of cultural, social, personal and psychological simultaneously on the decision of housewives to shop at Alfamart Banjarmasin, (b) determine the influence of cultural, social, personal and psychological partially on the decision if housewives to shop at Alfamart Banjarmasin, and (c) determine among cultural, social, personal and psychological which has dominant influence on the decision housewives to shop at Alfamart Banjarmasin. This type of research used is included as survey research. The population in this study is housewives shopping at Alfamart. The number of samples in this study is 80 housewives as respondents. The data used is quantitative and qualitative data, while the data source is primary and secondary data. The technique of collecting data through observation, questionnaires, and literature. Data analysis techniques modeled using multiple regression analysis, which refers to the econometric model. Based on the analysis, simultaneously cultural, social, personal and psychological factors influence the decision of housewives shopping at Alfamart. Four independent variables are able to explain the effect of housewives’ decision shopping at Alfamart amounted to 60.3%. Partially cultural, social, personal and psychological factors influence the decision if housewives shopping at Alfamart. Personal factor is the most dominant variable influencing the decision of housewives shopping at Alfamart.